A Study on the Process and Effectiveness of Investigative Video Storytelling - Raguram, S.; Rasmin, M.C.; Azad, M. (My University, 2017)
Investigative journalism in its true sense plays a key role in maintaining accountability and transparency on issues affecting people in general. The recent studies conducted by International Institute of War and Peace Reporting (IWPR, 2017), International Research Exchange Board (IREX, 2017,) International Media Support (IMS, 2017) and Free Media Movement (FMM) observed that investigative journalism in Sri Lanka is growing slowly while facing a systemic challenge, as a result of weak media pluralism, lack of editorial independence, political and commercial orientation of media ownership, insecurity, impunity and a lack of enabling policy environment etc. Adding a different dimension, the Investigative Video Storytelling program – #IVS, initiated by Sri Lanka Development Journalist Forum (SDJF) in partnership with IWPR and Postgraduate Institute of Agriculture, University of Peradeniya, intents to capacitate 25 young mid-career journalists who are interested in using videos as a potential tool to produce investigative stories on issues with public interest and issues that are often excluded by the mainstream media. The project was designed with the purpose of experimenting as to how the concept of investigative journalism works in the context of video. SDJF with its partner organizations intended to learn from the process of making investigative video stories to determine opportunities and challenges. This study not only concentrated on understanding the process and its effectiveness of investigative video story making program but also tried to determine the possible threats and opportunities existing for investigative reporting in Sri Lanka.